Human Resource Development for Prevention and Care of Fistula:Experience of University Fistula Center, BSMMU - Chowdhury, Saleha Begum; Huda, SkNazmul; Mahmud, Sharmeen (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: The purpose of this presentation is to share the experience of doctors and nurses training on prevention and care of fistula at University Fistula Center (UFC), BSMMU. Methods: From June 2016 to June 2018, UFC implemented training for doctors using a FIGO curriculum and for nurses using an EngenderHealth curriculum. The training and performance data have been captured using an aggregated DHIS2 database developed by the Fistula Care Plus (FC+) Project at EngenderHealth, FC+ Safe Surgery Toolkit, and regular narrative reports. Results: In this period, 11 surgeons were provided with basic and refresher training through four structured courses. Additionally, 16 nurses were provided training and refresher training on fistula nursing. Conclusions: The multicenter approach for fistula training was found to be helpful in creating more opportunities for hands-on experience and developing partnerships for inter-institutional capacity sharing for fistula services.